Medicolegal Evaluation of Elderly Trauma Patients - Durak, Dilek; Ural, Mustafa Numan; Fedakar, Recep; Gürses, Murat Serdar; Akan, Okan; İnanır, Nursel Türkmen; Çetin, Selçuk (The Bulletin of Legal Medicine, 2016)
Objective: The human body loses flexibility and durability from the pathophysiological changes of aging; therefore, trauma and the risk of injury increase in geriatric individuals. Elderly patients who have been admitted to health centers with trauma and injury require a serious treatment approach.Materials and Methods: A total of 15851 victims who were admitted to Bursa Branch of the Council of Forensic Medicine of the Ministry of Justice between 01/01/2011 and 31/12/2011 were retrospectively evaluated, and 207 of them, who were trauma patients aged 65 years and over, were included in this study. All cases were evaluated according to the cause of the injury, localization of the trauma, bone fractures and type of medical treatment. Results: Two hundred nineteen of the total 15851 forensic patients were 65 years and older. Of these 219 cases, 207 (94.5%) had been exposed to trauma. Of these 207 cases, 138 (66.7%) were male, and 69 (33.3%) were female. The most common types of trauma were physical assault (n=136) and motor vehicle accidents (n=56), which occurred at rates of 65.7% and 27.1%, respectively. For the trauma victims, head injury was the most commonly affected body region. Ninety-seven patients were treated conservatively (46.9%), and 43 patients were treated surgically (20.8%). Traumatic bone injury (31%) was detected in 64 patients.Conclusion: The results of our study indicate that most of the geriatric victims were admitted to the medical centers with traumatic causes. Thus, it is necessary to increase our social sensitivity to trauma and the ways in can be prevented in the geriatric age group.Key words: Trauma; Geriatric; Forensic case; Injury.
Keywords: trauma; geriatric; forensic case; injury